HERMENEUTIC METHOD: SOLUTIONS TO FIQH MUAMALAH CONTEMPORARY PROBLEMS - Afriadi, Wawan; Pati, Surya (JURNAL ILMU SYARIAH, 2021)
The fiqh muamalah discourse is not immune from the demands of reform by not being controlled by the monotonly that narrows the scope of Muslims thinking. This study examines the relevance of the use of Islamic hermeneutics to answer fiqh muamalah contemporary problems, especially the issue of the concept of riba and bank interest by using the Islamic hermeneutic method of Fazlur Rahman and Muhammad Syahrur. This research is library one of which research data sources come from primary and secondary sources. The primary data sources are the works of Rahman and Syahrur, while the secondary data sources are articles, journals, books. The data analysis method used is a qualitative descriptive method. The description of the research data is divided into several stages, namely; Islamic hermeneutics against the monotony of thought, fiqh muamalah in contemporary, riba and bank interest issues the thoughts of Fazlur Rahman’s and Muhammad Syahrur’s.